Determinations of gas–liquid partition coefficients using capillary chromatographic columns. Alkanols in squalane - Tascon, Marcos (2013)
This study focused on an investigation into the experimental quantities inherent in the determination of partition coefficients from gas–liquid chromatographic measurements through the use of capillary columns.Wepreparedseveral squalane – (2,6,10,15,19,23-hexamethyltetracosane) – containing columns with very precisely known phase ratios and determined solute retention and hold-up times at 30, 40, 50 and 60 ◦C. We calculated infinite dilution partition coefficients from the slopes of the linear regression of retention factors as a function of the reciprocal of the phase ratio by means of fundamental chromatographic equations. In order to minimize gas–solid and liquid–solid interface contributions to retention, the surface of the capillary inner wall was pretreated to guarantee a uniform coat of stationary phase. The validity of the proposed approach was first tested by estimating the partition coefficients of n-alkanes between n-pentane and n-nonane, for which compounds data from the literature were available. Then partition coefficients of sixteen aliphatic alcohols in squalane were determined at those four temperatures. We deliberately chose these highly challenging systems: alcohols in the reference paraf- finic stationary phase. These solutes exhibited adsorption in the gas–liquid interface that contributed to retention. The corresponding adsorption constant values were estimated.We fully discuss here the uncertainties associated with each experimental measurement and how these fundamental determinations can be performed precisely by circumventing the main drawbacks. The proposed strategy is reliable andmuchsimpler thanthe classical chromatographicmethod employing packed columns.